Regulation of transcription in Plasmodium falciparum, the causative agent of severe malaria: initial characterisation of PfTBP and PfTFIIA - Milton, Robert A (Department of Molecular and Cell Biology, 2018)
Malaria, caused by Plasmodium parasites, remains a leading cause for morbidity and mortality worldwide, resulting in more than 430 000 deaths annually. P. falciparum is responsible for the vast majority of severe malaria cases, accounting for more than 90% of malaria-related fatalities, predominantly in subsaharan Africa. The parasite has a complex life cycle, which involves transitioning between multiple distinct morphologies. The severity of the disease is brought about by the variable expression of parasite proteins on the surface of infected red blood cells. The substantial morphological changes, together with the variable expression of cell surface proteins, are governed by tightly controlled stage-specific changes in gene expression patterns. Understanding the regulatory mechanisms that govern these changes is crucial to fully understanding the parasites biology and pathology at the molecular level, a key step toward identifying targets for the development of much needed novel antimalarial drugs. Ultimately, all gene regulatory mechanisms converge to regulate the assembly and function of the RNA polymerase II (RNAP-II) transcription initiation complex composed of RNAP-II and the general transcription factors (GTFs). Bioinformatics analyses show that the RNAP-II GTFs in P. falciparum have greatly diverged from those studied in other eukaryotes, suggesting the existence of parasite-specific gene regulatory mechanisms, which have so far not been studied. This research project concerns the structure and function of P. falciparum TBP, TLP and TFIIA, key proteins involved in core promoter recognition, the first step in RNAP-II transcription initiation complex assembly. The work provides strong evidence for the existence of two different PfTFIIA complexes containing different PfTFIIA-γ subunits. The data further demonstrate that PfTBP and PfTLP DNA-binding activities differ distinctly from the classical TBP-DNA interactions seen in other eukaryotes and demonstrate interaction with and stimulation of PfTBP and PfTLP DNA-binding activity by one of the two PfTFIIA complexes. The work represents a first step towards understanding the regulation of transcription initiation in P. falciparum, gives first insights into Plasmodium-specific features, and provides a solid foundation for further investigations into this crucial aspect of malaria biology.